Single monoclonal spike characterized as double monoclonal gammopathy in a patient with multiple myeloma: A rare finding - Rajni Saijpaul; Vatsala Khurana; Rashmi Verma; Smita Kaushik (Wolters Kluwer Medknow Publications, 2024)
Multiple myeloma (MM) is associated with the secretion of a unique monoclonal protein (M-protein) due to overproduction of immunoglobulin (Ig) by a clone of abnormally proliferating plasma cells. However, in 4% of the cases more than one M-protein can be found. This category of gammopathies is called "double monoclonal gammopathies." Here, we present a rare case of MM with double monoclonal gammopathy, where the presence of both M-proteins was observed in the single sharp peak on capillary zone electrophoresis (CZE). Further the interference of Hook effect is also discussed. Double monoclonal gammopathies need to be identified to increase diagnostic accuracy and reliability, and to get a better understanding of the disease pathogenesis and progression.